Is it enough to utilize a single anchor for repair of rotator cuff tears ≤ 3 * 3 cm²? - Ala’ Hawa; Alexander Tham; James Bilbrough; Christyon Hayek; Mina Shenouda; George A. C. Murrell (PLoS ONE, 2025)
Background Biomechanical studies showed that increasing number of anchors could improve the repair strength of the repaired cuff at time zero. Purpose The aim of this study was to determine if utilizing only a single anchor for a cuff tear repair is sufficient or otherwise to give a similar retear rate and clinical outcome as multiple anchors in a matched group of patients. Study design Cohort study; Level of evidence, 3. Methods Retrospective analysis of 346 matched consecutive patients (single anchor group, n = 173; multiple anchors group, n = 173) who had cuff tears ≤ 3*3 cm² (mediolateral * anteroposterior diameters) repaired by a single senior surgeon. Ultrasound was used to evaluate the integrity of repair 6 months post-surgery. Patient and surgeon reported outcomes were used to evaluate the clinical outcome of the method used for repair. Results 6 months post-surgery; the retear rate for cuff tears ≤ 1*1 cm², tears ≤ 1 cm in mediolateral diameter and > 1 cm in anteroposterior diameter and tears > 1 cm in mediolateral diameter and ≤ 1 cm in anteroposterior diameter was similar in single and multiple anchors groups (4.8%) (3.3%) (P = 1.00), (10.8%) (7.9%) (P = 0.71) and (0%) (0%) respectively. Retear rate for cuff tears > 1*1 cm² was significantly higher in single anchor group (25.4%) compared to multiple anchors groups (10.9%) (P < 0.05). Operative time was significantly lower in single anchor group (14 minutes) compared to multiple anchors group (20 minutes) (P < 0.05) only for cuff tears ≤ 1*1 cm². Conclusion 6-months post-surgery; there was no significant difference in retear rate or clinical outcome between patients with tears ≤ 3*3 cm² (mediolateral * anteroposterior diameters) who had their cuff tears repaired using a single anchor compared to those who had their cuff tears repaired using multiple anchors unless both the mediolateral and anteroposterior diameters of the tear were > 1 cm, for which the utilization of multiple anchors showed a significantly lower retear rate at 6 months post-surgery. Operative time was significantly shorter only when a single anchor was used for repair of tears ≤ 1*1 cm².